Putative chemosensory receptors of the codling moth, Cydia pomonella, identified by antennal transcriptome analysis. - Jonas M Bengtsson (Public Library of Science (PLoS), 2012)
The codling moth, Cydia pomonella, is an important fruit pest worldwide. As nocturnal animals, adults depend to a large extent on olfactory cues for detection of food and mates, and, for females, oviposition sites. In insects, odor detection is mediated by odorant receptors (ORs) and ionotropic receptors (IRs), which ensure the specificity of the olfactory sensory neuron responses. In this study, our aim was to identify chemosensory receptors in the codling moth as a means to uncover new targets for behavioral interference. Using next-generation sequencing techniques, we identified a total of 43 candidate ORs, one gustatory receptor and 15 IRs in the antennal transcriptome. Through Blast and sequence similarity analyses we annotated the insect obligatory co-receptor ORco, five genes clustering in a conserved clade containing sex pheromone receptors, one homolog of the Bombyx mori female-enriched receptor BmorOR30 (but no homologs of the other B. mori female-enriched receptors) and one gene clustering in the sugar receptor family. Among the candidate IRs, we identified homologs of the two highly conserved co-receptors IR8a and IR25a, and one homolog of an IR involved in phenylethyl amine detection in Drosophila. Our results open for functional characterization of the chemosensory receptors of C. pomonella, with potential for new or refined applications of semiochemicals for control of this pest insect.